Penile warts: an update on their evaluation and management - Alexander KC Leung; Benjamin Barankin; Kin Fon Leong; Kam Lun Hon (BioExcel Publishing Ltd, 2018)
Background: Penile warts are the most common sexually transmitted disease in males. Clinicians should be familiar with the proper evaluation and management of this common condition. Objective: To provide an update on the current understanding, evaluation, and management of penile warts. Methods: A PubMed search was completed in Clinical Queries using the key terms 'penile warts' and 'genital warts'. The search strategy included meta-analyses, randomized controlled trials, clinical trials, observational studies, and reviews. Results: Penile warts are caused by human papillomavirus (HPV), notably HPV-6 and HPV-11. Penile warts typically present as asymptomatic papules or plaques. Lesions may be filiform, exophytic, papillomatous, verrucous, hyperkeratotic, cerebriform, fungating, or cauliflower-like. Approximately onethird of penile warts regress without treatment and the average duration prior to resolution is approximately 9 months. Active treatment is preferable to watchful observation to speed up clearance of the lesions and to assuage fears of transmission and autoinoculation. Patient-administered therapies include podofilox (0.5%) solution or gel, imiquimod 3.75 or 5% cream, and sinecatechins (polypheron E) 15% ointment. Clinicianadministered therapies include podophyllin, cryotherapy, bichloroacetic or trichloroacetic acid, oral cimetidine, surgical excision, electrocautery, and carbon dioxide laser therapy. Patients who do not respond to first-line treatments may respond to other therapies or a combination of treatment modalities. Second-line therapies include topical/intralesional/ intravenous cidofovir, topical 5-fluorouracil, and topical ingenol mebutate. Conclusion: No single treatment has been shown to be consistently superior to other treatment modalities. The choice of the treatment method should depend on the physician's comfort level with the various treatment options, the patient's preference and tolerability of treatment, and the number and severity of lesions. The comparative efficacy, ease of administration, adverse effects, cost, and availability of the treatment modality should also be taken into consideration.